Clearing, settlement and custody - Loader, David (Butterworth-Heinemann, 2020)
Clearing, Settlement, and Custody, Third Edition, introduces the post-trade infrastructure and its institutions. Author David Loader reduces the complexity of this environment in a non-technical way, helping students and professionals understand the complex chain of events that starts with securities trading and ends the settlement of cash and paper. The Third Edition examines the roles of clearing houses, central counterparties, central securities depositories, and custodians. The book assesses the impact on workflow and procedures in the operations function at banks, brokers, and institutions. In consideration of technological and regulatory advances, this edition adds 5 new chapters while introducing new case studies and updating examples.